Challenges and Opportunities in Implementing the MATATAG Curriculum: A Scoping Review - Herrera, Nico Jay N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study utilized a scoping review to provide an overview of empir-ical studies on the implementation of the MATATAG curriculum in the Philippines. The review covered eleven studies published in 2024 that qualified in the inclusion and exclusion criteria . The majority of the studies were qualitative in nature and were subjected to descriptive and content analyses. The results of this review revealed five themes: teachers’ perspectives, school heads’ perspectives, training experi-ences, challenges encountered and teaching and leading with resilien-cy. The findings express that the successful implementation of the MATATAG curriculum in the Philippines depends on teachers' and school heads' experiences, effective training programs, and ongoing professional development, emphasizing the need for policy support and adaptive strategies to enhance resilience and sustain curriculum reforms in a supportive educational environment.